Implementation of community cohesion policy in Italy and its role in elimination of regional disparities - Lewandowski, Krzysztof (Comparative Economic Research. Central and Eastern Europe, 2011)
The objective of this paper is to present the contribution of Community regional policy funds to achieving socio-economic cohesion of Italian regions eligible under Objective 1, as well as to discuss future development barriers and opportunities of these regions. The paper also provides a description of Italy's adjustment to the Community policy, the funds exploited by cohesive regions during the 2000-2006 programming period and their efficiency in the elimination of regional disparities.